Iron oxide nanoparticles as radiobiological dose enhancer for radiotherapy - Lazim, Rosmazihana Mat (2016)
Introduction: Iron oxide nanoparticles (IONPs) have extensively been investigated as contrast agents for magnetic resonance imaging (MRI) and other promising biomedical application such as targeted drug delivery. The intriguing properties of IONPs not only promising for multimodality diagnostic application but also for therapeutic purpose especially radiotherapy. In this thesis, potential application of IONPs to increase the efficiency of radiotherapy outcome was investigated and explored. Methods: The study is conducted in-vitro using T24 bladder cancer cells, HCT116 human colon carcinoma cell lines and F98 rat glioma cells with 15 nm IONPs. The evaluation on the cytotoxicity was initially conducted to ensure the IONPs biocompatibility to the cells. Investigation on the dose enhancement were done by irradiating the cells with and without 1mMol/L of IONPs using photon, electron, proton and synchrotron’s kilovoltage monoenergetic x-rays beams of different energies and doses. The cell survival curves were obtained using standard clonogenic assay and were analyzed using linear quadratic model. Dose enhancement factor (DEF) were extrapolated at 90% cell survival and calculated from the survival curves.Results and discussions: Cytotoxicity test indicate in vitro biocompatibility of IONPs. IONPs were observed to induce dose enhancement effects in all different types of radiotherapy beam tested except the electron beam. Photon beam of energy 6 MV and 10 MV show dose enhancements of 1.71-2.50 folds in the presence IONPs. Meanwhile, the high LET heavy ion of proton beam indicate higher enhancement factor closed to 2 fold. Synchrotron’s kilovoltage monoenergetic x-rays beam indicates highest doseenhancement effects with DEF value 9.11. However, irradiation with electron beams does not produce any significant dose enhancement effects which could be link to the lack of interaction that induce free radical and reactive oxygen species (ROS) that enhance the cell’s death. Conclusions: The IONPs are found to be effective as dose enhancer for cancer treatment using different types of ionizing radiation and energy ranges except for electron beam therapy. The effects are more pronounced for synchrotron kilovoltage monoenergetic x-rays beam and proton beam suggesting the potential new technique for IONPs clinical application. The outcome from this thesis implying the clinical potential of IONPs in increasing the radiotherapy efficiency to treats cancer. Keywords: iron oxide nanoparticles, dose enhancement, radiotherapy